The Role of Technology-Based Review Management in Mediating the Influence of Online Reviews on Hotel Brand Image and Guest Loyalty at Ayodya Resort Bali - I Putu Budiarsa; Ni Made Yudhaningsih; Wayan Ardani (PT FORMOSA CENDEKIA GLOBAL, 2026)
The global hospitality industry has undergone a profound digital transformation, positioning online reviews as decisive influencers of traveller decisions. At the same time, the emergence of fraudulent review practices prompted six major platforms Amazon, Booking.com, Expedia Group, Glassdoor, Tripadvisor, and Trustpilot to establish the Coalition for Trusted Reviews in October 2023, underscoring the strategic urgency of authentic digital reputation management. This study investigates the role of technology-based review management as a mediator in the relationship between online guest reviews and two critical outcomes: hotel brand image and guest loyalty. Data were collected from 96 purposively sampled respondents guests who stayed at the resort within the preceding 12 months and analysed through Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS 4.0. Of the seven hypotheses tested, six were supported. Online reviews positively and significantly influenced both brand image (β = 0.589, p < 0.001) and guest loyalty (β = 0.441, p < 0.001). Technology-based review management likewise exerted significant positive effects on brand image (β = 0.258, p = 0.003) and guest loyalty (β = 0.474, p < 0.001). findings have strategic implications for luxury hospitality operators seeking competitive differentiation through technology-enabled reputation innovation.